What do home videos tell us about early motor and socio-communicative behaviours in children with autistic features during the second year of life: an exploratory study - Zappella, Michele; Bölte, Sven (Early human development, 2015)
Background: Little is known about the first half year of life of individuals later diagnosed with autism spectrum disorders (ASD). There is even a complete lack of observations on the first 6months of life of individuals with transient autistic behaviours who improved in their socio-communicative functions in the pre-school age. Aim: To compare early development of individuals with transient autistic behaviours and those later diagnosed with ASD. Study design: Exploratory study; retrospective home video analysis. Subjects: 18 males, videoed between birth and the age of 6months (ten individuals later diagnosed with ASD; eight individuals who lost their autistic behaviours after the age of 3 and achieved age-adequate communicative abilities, albeit often accompanied by tics and attention deficit). Method: The detailed video analysis focused on general movements (GMs), the concurrent motor repertoire, eye contact, responsive smiling, and pre-speech vocalisations. Results: Abnormal GMs were observed more frequently in infants later diagnosed with ASD, whereas all but one infant with transient autistic behaviours had normal GMs (p<0.05). Eye contact and responsive smiling were inconspicuous for all individuals. Cooing was not observable in six individuals across both groups. Conclusions: GMs might be one of the markers which could assist the earlier identification of ASD. We recommend implementing the GM assessment in prospective studies on ASD.